LaVonne C.

# how can i tell when to use the foil method?

whats the difference between foiling and distributing?

## 3 Answers By Expert Tutors

By: Tutor
New to Wyzant

Math and Excel Tutor - elementary school up to middle school subjects Tutor
5 (3)

Tutoring in Precalculus, Trig, and Differential Calculus

Kay G.

Your foil one IS distribution.  This gives the impression that foil is something besides distribution.
Report

04/08/14 Parviz F.

I just avoid FOIL all together, it is just useless memorization of irrelevance:

Multiply 2 binomial

( X + a ) ( X +b)

Just distribute it twice:

( X +a) X + b( X +a) = X ^2 + aX + bX + ab

Then factor by Grouping:

X^2 + ( a + b ) X + ab

Then it comes useful in factoring Quadratic and solving for roots

f( X) =  X ^2 + ( a + b ) X + ab = ( X +a ) ( X +b )

f( x ) = 0   ( X +a ) = 0   X1 = -a     ( X +b) = 0   X2 = -b

Substituting back ( X, X2 ) into f( X)

f( X) = X^2 - ( X1 + X 2 ) X + X1X2     (2)

Where aX^2 + bX + c = 0

always   X1 + X2 = - b/a   X1 . X2= c/a (3)

Relationship ( 3) is the key Principle that leads to the solution of quadratic and even polynomial'

that should be emphasized instead of FOIL.

Report

04/08/14

## Still looking for help? Get the right answer, fast.

Get a free answer to a quick problem.
Most questions answered within 4 hours.

#### OR

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.